The Effectiveness Of Teaching Reading Comprehensions Using Jigsaw Compared To Using Sq3r Of Smpn 1 Banyakan - Yanti Rasmiasih (LPPM IAI Hasanuddin Pare-Kediri, 2019)
The purpose of this research is to know Is there any significant effect when they are taught Reading Comprehensions by using JIGSAW and using SQ3R. The design used quasi-experimental research design. It was conducted in SMPN 1 BANYAKAN. The headmaster just gives two classes for the researcher. So the reseracher used two classes thre are: the class VII -D as experimental 1 and the class VII - C as experimental 2. The instrument was used. in this research the researcher used test both pre and post. The data gotten was analyzed by SPSS version 15.00 to find descriptive and effective before and after treatment. The result of the research are: independent T-test analysis the sig is 0.412 then the sig (2-tailed ) is .000. T value 6.325 is higher than the minimum requirement 2.65. so it can be condlude that the alternative hypothesis is “There is significant influence difference between students’ reading comprehension of using SQ3R better in reading comprehension than using Jigsaw to the First grades of SMPN 1 BANYAKAN.” Is accepted than the null hypothesis is rejected. It can be conclude that teaching reading comprehension using SQ3R more efective that Jigsaw in the first grade SMPN 1 Banyakan.